2016
DOI: 10.17221/290/2015-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Innovative approaches to examining consumer preferences when choosing wines

Abstract: Consumer neuro-science is a new fi eld in marketing, which aims to predict the consumer behaviour and to obtain information about feelings and preferences based on the physiological changes. We can objectively reveal our inexplicable behaviour to which we are not able to answer using a questionnaire in the traditional market research. An accurate measurement enables marketers to compare the response during research, such as the impact moments associated with a particular product or brand, how they react to dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 23 publications
0
30
0
2
Order By: Relevance
“…[102,123,218,280] Education These articles tracked students' engagement and learning. [38,281] Assistance These articles explored how assistive technologies or learning resources were provided to individuals.…”
Section: Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…[102,123,218,280] Education These articles tracked students' engagement and learning. [38,281] Assistance These articles explored how assistive technologies or learning resources were provided to individuals.…”
Section: Monitoringmentioning
confidence: 99%
“…Because customer feelings in sales areas are strongly influenced by the perception of the surroundings, recognition of emotional responses can reveal true consumer preferences and improve and assist in the (buying) process. Four articles have presented this idea in different applications [102,123,218,280].…”
Section: Domain Description Referencesmentioning
confidence: 99%
“…Another study observed and discussed gender differences during wine consumption, with both EEG and AFEA results showing stronger emotional responses from female participants. Some researchers recommend specific sample demographics matched to specific categories, such as female sample pools for wine evaluation [56].…”
Section: Population Influencementioning
confidence: 99%
“…En referencia a las emociones producidas por el vino, en varios estudios se ha demostrado que los consumidores sienten emociones positivas y negativas al catar vino (Horska et al, 2016) o al pensar en su consumo y han establecido el poder de estas emociones para segmentar a los consumidores (Silva et al 2016). Por su parte, Dhar y Wertenbroch (2000) demostraron que los aspectos emocionales pueden conllevar a que una persona compre un vino sólo para probarlo, aunque en principio piense que sea una mala elección.…”
Section: Influencia De Las Emociones Generadas Por La Oferta De Vino unclassified